A Case of Mycobacterial Skin Disease Caused by Mycobacterium peregrinum, and a Review of Cutaneous Infection - Fuminao Kamijo; Hisashi Uhara; Hitomi Kubo; Kazue Nakanaga; Yoshihiko Hoshino; Norihisa Ishii; Ryuhei Okuyama (Karger Publishers, 2012)
An 83-year-old Japanese man presented with a 2-month history of symptomatic nodules on the left hand. He was not in an immunocompromised condition and reported no causal events. A biopsy specimen demonstrated granulomatous tissue with mixed cell infiltration consisting of neutrophils, histiocytes, lymphocytes, and multinuclear giant cells. No bacillus was detected by PAS, acid-fast stain, immunofluorescent stain or polymerase chain reaction analysis. The isolate was found to be a rapidly growing mycobacterium after 4 weeks of incubation at 25°C on an Ogawa egg slant. Mycobacterium peregrinum was isolatedby DNA-DNA hybridization analysis, 16S rRNA gene sequence, and by its production of 3-day arylsulfatase. The patient received 200 mg oral minocycline for 28 weeks. The lesion disappeared after 10 weeks of this treatment.